Synthesis of PMMA-PEG@TiO2 nanocomposite by hydrothermal and sol-gel techniques for resveratrol delivery - Annaraj, Jamespandi (Malaysian NANO-An International Journal, 2024)
TiO2 nanoparticles were prepared using the sol-gel and hydrothermal procedures in order to compare their porosity, stability, and particle homogeneity as well as their encapsulation efficiency. Alcohol is converted into gel using the sol-gel method, which involves stirring it while it’s hot, then drying, powdering, and calcining it. This simple process produces high-purity products, however due to agglomeration, it also produces unpredictable particle size and shape. On the other hand, hydrothermal approach requires enormous volumes at high pressure, which makes it slow and difficult to scale up. However, it is effective in producing uniform nanoparticles. Nanoparticles were synthesized using both methods to evaluate differences in drug loading and releasing capacities. TiO2 was chosen for its excellent biocompatibility, mechanical strength, and chemical resistance, as well as its documented anticancer activity. To prevent premature drug release, the TiO2 nanoparticles were coated with a copolymer of Poly(methyl methacrylate) and Polyethylene glycol (PMMA-PEG), which forms a mesh-like structure that enhances drug absorption and loading capacity. The drug Resveratrol was used in this study. The synthesized nanoparticles were characterized using X-ray diffraction (XRD), ultraviolet-visible spectroscopy (UV-Vis), and scanning electron microscopy (SEM) to analyze their structural and morphological properties. These characterization results facilitated the determination of the most effective synthesis method for creating TiO2 nanoparticles with superior anticancer activity.